Pengaruh Self-Regulated Learning terhadap Student Engagement pada Mahasiswa Program Studi Ilmu Hukum - Fasya Dhiyatamma Putri; Yuli Aslamawati (Bandung Conference Series: Psychology Science, 2022)
Abstract. This study aims to determine the effect of self-regulated learning on student engagement in students of law study program in Bandung. Self-regulated leaning is an active and constructive process in which students can set learning goals by monitoring, regulating, and controlling cognition, motivation, and behavior, so that they always focus on the goals (Pintrich, 2004). Student engagement is the involvement of students in the learning process, both in academic activities and non-academic activities, which are seen through behavior, emotion, and cognition (Fredricks, 2004). This study uses quantitative research with a casual approach (cause and effect). The sampling technique used in this study is proportionate stratified random sampling. Data collection was carried out by using a questionnaire that involved two measuring instruments, namely Motivated Strategies for Learning Questionnaire (MSLQ) with the reliability of 0.916 and University Student Engagement Inventory (USEI) with the reliability of 0.882. In this study, there were 378 active students of law study program in Bandung. Data analysis was carried out by using simple linear regression statistical analysis, with the help of SPSS Statistics 23.0. The results of the analysis show that there is a significant effect of self-regulated learning on student engagement, which is seen from the sig. (0.000 > 0.05). The contribution of the effect is 0.517 or 51.7%. From the results of the regression analysis equation, it is also found that the equation is Y = 5.294 + 0.213X. The equation shows that there is a positive effect of self-regulated learning (X) on student engagement. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh self-regulated learning terhadap student engagement pada mahasiswa program studi ilmu hukum Kota Bandung. Self-regulated leaning adalah proses aktif dan konstruktif dimana pelajar dapat menetapkan tujuan pembelajaran dengan cara memantau, mengatur, mengendalikan kognisi, motivasi, dan perilaku agar selalu tertuju pada tujuan (pintrich, 2004). Student engagement adalah keterlibatan yang dilakukan oleh pelajar dalam proses pembelajarannya baik pada kegiatan akademik dan kegiatan non akademik yang terlihat melalui tingkah laku, emosi, dan kognitif (Fredricks, 2004). Penelitian ini menggunakan penelitian kuantitatif dengan pendekatan kausal (sebab akibat). Teknik sampling yang digunakan dalam penelitian ini adalah proportionate stratified random sampling. Pengumpulan data dilakukan menggunakan kuesioner yang melibatkan dua alat ukur, yaitu Motivatied Strategies for Learning Quiestionnaire (MSLQ) dengan reliabilitas 0,916 dan University Student Engagement Inventory (USEI) dengan reliabilitas 0,882. Dalam penelitian ini terdapat 378 mahasiswa aktif program studi ilmu hukum Kota Bandung. Analisis data yang dilakukan menggunakan analisis statistik regresi linear sederhana dengan bantuan program SPSS 23.0. Hasil analisis menunjukkan bahwa terdapat pengaruh yang signifikan antara self-regulated learning terhadap student engagement dilihat dari sig. (0.000 > 0.05). Sumbangan pengaruhnya sebesar 0.517 atau 51,7%. Dari hasil persamaan analisis regresi juga didapatkan persamaan yaitu Y = 5,294 + 0,213X. Persamaan tersebut menunjukkan bahwa terdapat pengaruh positif antara self-regulated learning (X) terhadap student engagement.